Preceptorship Program and Recruitment Process on Improving the Behavior of Professional Nurses in the Inpatient Room of Hospital C Jakarta - Retno Susanti; Asnet Leo Bunga; Sudibyo Supardi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: The unprofessional behavior of nurses makes nursing services not provide positive values, which can be influenced by the absence of preceptorship for nurses. The research conducted in June – August 2022 aims to assess the effect of preceptorship program and recruitment process to improve professional nurse behavior. Design: Quasi-experimental study, with intervention group preceptorship program RS Cinta Kasih Tzu Chi and control group RS Mentari. Samples of intervention and control groups were 35 respondents each, using total sampling technique. Data collection tools are questionnaires and pretest - posttest data collection is carried out 4 days after the questionnaires are distributed. Method: Data analysis using Wilcoxon test, Chi-square test and multivariate logistic regression test. Results: The results showed that the behavior of professional nurses increased. There are differences in the behavior of nurses in the intervention and control groups (p value= 0.000). There is the relationship between the recruitment process and an increase in the behavior of nurses (p value = 0.001). Working period (p value = 0.017) and preceptorship program (p value = 0.006) have an effect on increasing the behavior of professional nurses. Conclusion: It is hoped that RS C will hold a preceptorship program and establish regulations, policies, guidelines and guidelines on the application of the preceptorship method to changes in the behavior of professional nurses. Nurses understand and instill the behavior of professional nurses starting from themselves, colleagues, and patient care.